Use of dietary fenugreek (Trigonella foenum-graecum L.) seed for the production of safe broiler lean meat - Toaha, Shah Mohammad; Mollah, Bazlur Rahman; Ahammad, Muslah Uddin (Research in Agriculture Livestock and Fisheries, 2016)
An experiment was conducted for a period of 28 days to determine the dietary effect of fenugreek seeds (FGS) on the productive and economic performances of broilers. A total of 400 day-old Hubbard Classic straight run broiler chicks were randomly allocated to 5 isonitrogenous and iso-caloric dietary treatment groups, each having 80 chicks in 4 replications of 20 numbers, in a completely randomized design (CRD). Broilers were fed ad libitum on either basal diet with (positive control) or without (negative control) 0.1% antibiotic (used as antibiotic growth promoter; AGP) or basal diet containing 1.0%, 2.0% or 3.0% FGS. There were no differences in live weight, feed intake and feed conversion ratio (FCR) among the treatment groups for broilers up to 14 days of age (P>0.05). Broilers fed on the diet containing FGS exhibited significantly better productive performances than those fed on AGP (P<0.01). However, the highest productive performances were recorded for the 2.0% FGSfed broilers in all treatment groups, followed by broilers received 1.0% and 3% FGS (P<0.01). Inclusion of dietary FGS at 2% level resulted in higher dressed carcass, breast, thigh and drumstick meat weight compared to any other level of the FGS inclusion in broiler diet (P<0.01). Unlike the AGP, addition of 2% FGS to the diet significantly reduced abdominal fat (P<0.01). With regard to economic performance, broilers fed on diet containing 2% FGS fetched highest profit in the dietary treatment groups. Inclusion of FGS in broiler diet resulted in lower feed cost and higher profit compared to the inclusion of AGP in the diet. It may be concluded that supplementation of FGS in diets may be useful for efficient and economic production of broiler. The inclusion of FGS at 2% level in broiler diet may be profitable in the production of lean meat of broilers. Res. Agric., Livest. Fish.3(2): 305-314, August 2016